2012
DOI: 10.1631/jzus.b1100272
|View full text |Cite
|
Sign up to set email alerts
|

Relative bioavailability and pharmacokinetic comparison of two different enteric formulations of omeprazole

Abstract: Abstract:In order to comply with the requirements for a drug listed in China, the study was developed to compare the pharmacokinetics and relative bioavailability of two different enteric formulations of omeprazole (OPZ) in healthy Chinese subjects. A total of 32 volunteers participated in the study. Plasma concentrations were analyzed by nonstereospecific liquid chromatography/tandem mass spectrometric (LC-MS/MS) method. After administration of a single 40-mg dose of the two OPZ formulations, the comparative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 13 publications
4
10
0
Order By: Relevance
“…In conclusion, the pharmacokinetic results of this study confirm earlier findings [4,7,16,20,21] and emphasize that it is advisable in future researches to assess the metabolic status by phenotyping subjects with an adequate test prior to conducting pharmacokinetic studies.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In conclusion, the pharmacokinetic results of this study confirm earlier findings [4,7,16,20,21] and emphasize that it is advisable in future researches to assess the metabolic status by phenotyping subjects with an adequate test prior to conducting pharmacokinetic studies.…”
Section: Resultssupporting
confidence: 89%
“…Because of the low bioavailability and high inter and intra individual variability in the absorption of Omeprazole, it is necessary to perform comparative bioavailability studies [3,7]. The aim of this study was to evaluate, in healthy Algerian volunteers, the rate and extent of absorption of a local generic Omeprazole formulation against that of the innovator product MOPRAL® from ASTRA ZENECA laboratories in order to evaluate the intra-subject variability of Omeprazole (Coefficient of variation intra-subject:…”
mentioning
confidence: 99%
“…The mean plasma concentration was higher under fasting conditions than with food 37 . These results are in line with those of previous reports on the pharmacokinetics of OME by Liu and coworkers (C max of 1330.46 ± 758.07 ng/mL) 38 . Other authors reported lower C max owing to lower doses of OME 24,39 .…”
Section: Discussionsupporting
confidence: 93%
“…Other authors reported lower C max owing to lower doses of OME 24,39 . The high inter-subject variability indicated by the error bars in Fig 2 is similar to the findings reported by other authors 22,38 , thus making them suitable for monitoring. and area values are given for OME and OME-D3.…”
Section: Discussionsupporting
confidence: 89%
“…Separated blood plasma samples were frozen and kept at −70 °C until analysis. The plasma concentrations of OME and 5‐OH OME were determined using the modified nonstereospecific liquid chromatography/tandem mass spectrometric (LC‐MS/MS) method . These compounds were isolated using a liquid‐extraction method, and 50 μL (1 µg/mL) of internal standard (4‐desmethoxy‐OME; Ramidus AB, Lund, Sweden) was added to 100 μL of plasma.…”
Section: Methodsmentioning
confidence: 99%